Visitors' involvement, perceived value, satisfaction and behavioural intention on tourist express trains in Taiwan. (10th March 2010) - Ho, Li-Hsing; Chung, Cheng-Wei; Lin, Shu-Ping; Chen, Lu-Fang
Taiwan tourism express has become a newly-developed industry. Due to the characteristics of invisibility and of simultaneous occurrence of the production and consumption, it might be difficult to estimate the advantages and disadvantages of consumption beforehand; tourists might purchase the product through consumers' involvement. This research discusses customers' involvement, perceived value, satisfaction, and purchase behaviour. Besides, multiple-group SEM analysis was used to analyse the types of operation between the tourism agencies. The results showed: the perceived value and purchase behaviour were influenced positively by the level of customers' involvement whereas the satisfaction is negatively influenced; purchase behaviour was not affected by perceived value directly, but could be influenced indirectly through the dimension of satisfaction. The tourists' purchase behaviour had been affected when they were involved in purchasing the products. The achievement developed by the single tourism agencies is better than that by the collective ones. Some of the tourists from different routes were willing to pay much more, while others were reluctant.